2022
DOI: 10.21037/atm-22-2536
|View full text |Cite
|
Sign up to set email alerts
|

Effect of micro-arc oxidation surface modification of 3D-printed porous titanium alloys on biological properties

Abstract: Background: Three-dimensional (3D) printing technology has been widely used in orthopedics; however, it is still limited to the change of macroscopic structures. In order to further improve the biological properties of 3D-printed porous titanium scaffolds, this study introduced micro-arc oxidation (MAO) technology to modify the surface of porous titanium scaffolds and construct bioactive coatings on the surface of porous titanium scaffolds to improve the biocompatibility and osseointegration ability of the mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…In the case of sample 136_450_n, the number of cells on the appropriate days of incubation was lower than that in the case of sample 136_450_rec. The cells are distributed more evenly on the UMAO coating than on the MAO coating, which may be related to the greater porosity and regularity of the microstructure of the UMAO coating . The cells are characterized by different morphologies depending on the incubation time.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of sample 136_450_n, the number of cells on the appropriate days of incubation was lower than that in the case of sample 136_450_rec. The cells are distributed more evenly on the UMAO coating than on the MAO coating, which may be related to the greater porosity and regularity of the microstructure of the UMAO coating . The cells are characterized by different morphologies depending on the incubation time.…”
Section: Resultsmentioning
confidence: 99%
“…The characterization results, surface morphology, and chemical composition of the coatings proved that the hybrid MAO-I 2 -PCLx coatings (x = 1, 2, 3) were successfully developed on the titanium alloy surface. After the micro-arc oxidation treatment, the titanium alloy gains a surface with a rich porous structure [ 38 , 39 ]. As the atomic force microscope showed, the surface roughness of the MAO substrate increases significantly, which creates a structural basis for the electrophoretic loading of iodine and the combination of the PCL coating in the later stage [ 40 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar experiments have shown that 8 weeks after the placement of Ti implants in adult rabbits, the pure Ti surface was still covered with fibrous tissue, while new bone formed on the surface of the titanium implants with MAO coating (Zhao et al, 2020). Other experiments have shown that MAO-coated implants have better bone-to-implant contact and coverage area attached to the implant, the highest density of newly grown paragenetic bone tissue, and can withstand greater shear (Chen et al, 2021;Ding et al, 2022;Ni et al, 2022). Wang et al's study demonstrated good osseointegration of the MAO coating was found by observing gross observation and micro-CT reconstruction of the femoral condyle after implant implantation and new bone formation was observed by toluidine blue and fuchsia-methylene blue staining.…”
Section: Osseointegrationmentioning
confidence: 99%